THE ROLE OF CROSS-CULTURAL COMMUNICATION COMPETENCE: EFFECTIVE TRANSFORMATIONAL LEADERSHIP ACROSS CULTURES - Lvina, Elena (SCAD Independent, 2015)
New theoretical frameworks are needed to better understand effective transformational leadership in different cultural contexts. In this article we illustrate the relationship between transformational leadership and the cross-cultural communication competence frame. We show how national culture orientations and cross-cultural communication competence affect the full range leadership framework and transformational leadership dimensions. Attributes of effective leadership and the choice of communication strategies vary for different cultural contexts; however, the charismatic or value-based leadership dimension contributes the most to universally perceived effective leadership styles. We draw attention to the importance of transformational leadership research utilizing the cross-cultural communication competence construct.